2017
DOI: 10.1063/1.4982900
|View full text |Cite
|
Sign up to set email alerts
|

Sloshing instability and electrolyte layer rupture in liquid metal batteries

Abstract: Liquid metal batteries (LMBs) are discussed today as a cheap grid scale energy storage, as required for the deployment of fluctuating renewable energies. Built as a stable density stratification of two liquid metals separated by a thin molten salt layer, LMBs are susceptible to short-circuit by fluid flows. Using direct numerical simulation, we study a sloshing long wave interface instability in cylindrical cells, which is already known from aluminium reduction cells. After characterising the instability mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 71 publications
(98 reference statements)
15
83
0
Order By: Relevance
“…It should be mentioned that criteria predicting instability onset for any non-vanishing Lorentz force neglect dissipative effects caused by magnetic induction and viscosity as well as the influence of surface tension [164].…”
Section: Interface Instabilitiesmentioning
confidence: 99%
“…It should be mentioned that criteria predicting instability onset for any non-vanishing Lorentz force neglect dissipative effects caused by magnetic induction and viscosity as well as the influence of surface tension [164].…”
Section: Interface Instabilitiesmentioning
confidence: 99%
“…The incompressible Navier-Stokes equation (NSE) for a Newtonian fluid is reformulated in order to take into account the multiphase nature of the system [63] as ∂(ρu) ∂t + ∇ · (ρuu) = −∇p d + gz∇ρ + ∇ · (ρν(∇u + (∇u) )) + f st (11) with ρ denoting density, u velocity, t time, g gravity acceleration, z the axial coordinate, ν kinematic viscosity and f st the source of momentum due to the surface tension. For the derivation of the modified pressure p d , see [24,63]. The interface capturing is done with the volume of fluid method (VOF), which uses a (volumetric) phase fraction α i for each fluid i.…”
Section: Thermo-fluid Dynamic Multiphase Solver and Discretizationmentioning
confidence: 99%
“…Several studies have shown that fluid motion can be triggered by magnetohydrodynamic effects, i.e., the interaction of a magnetic field (either a background field or the field caused by the battery current) with the cell current. This includes the Tayler instability [11][12][13][14][15][16], electro-vortex flows [17][18][19][20][21] as well as interface instabilities [22][23][24][25][26][27]. While the Tayler instability will get substantial only for large system (in the order of meters) [14], electro-vortex flow will appear already in small cells [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The governing equations for the magnetic field and the flow dynamics will be presented in detail in the next section. Parts of our implementation in foam-extend were developed in close relation with [16], specially regarding the flexible and efficient application of Biot-Savart's law (c.f. chapter 3) and a multi-mesh concept to address problems with several coupled physical effects, which are each valid on different (possibly overlapping) domains.…”
Section: Modelingmentioning
confidence: 99%